2021
DOI: 10.3390/ijerph18179344
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Students’ Mental Health and Sleep in Saudi Arabia

Abstract: Background: Mental health problems are prevalent among university students in Saudi Arabia. This study aimed to investigate the impact of the COVID-19 pandemic on university students’ mental health and sleep in Saudi Arabia. Method: A total of 582 undergraduate students from Saudi Arabia aged between 18 and 45 years old (M = 20.91, SD = 3.17) completed a cross-sectional online questionnaire measuring depression, anxiety, stress, resilience, and insomnia during the COVID-19 pandemic (2020). Analysis included an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
59
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 56 publications
9
59
2
5
Order By: Relevance
“…Past medical history, country of stay during the outbreak of COVID 19, and sleep hygiene scores were subsequently entered at the third step. 46 The strengths of associations were estimated by the beta coefficient. Additionally, effect sizes of regression analyses (ie, Cohen’s f 2 ) were calculated using an R 2 value to identify clinically significant associated factors.…”
Section: Descriptions Of Shi Gad-7 and Pss-10 Questionnairesmentioning
confidence: 99%
“…Past medical history, country of stay during the outbreak of COVID 19, and sleep hygiene scores were subsequently entered at the third step. 46 The strengths of associations were estimated by the beta coefficient. Additionally, effect sizes of regression analyses (ie, Cohen’s f 2 ) were calculated using an R 2 value to identify clinically significant associated factors.…”
Section: Descriptions Of Shi Gad-7 and Pss-10 Questionnairesmentioning
confidence: 99%
“…Earlier in the pandemic, COVID-19 had similar psychological impacts, particularly an increase in the proportion of persons reporting moderate to severe psychological impact among Saudi Arabia's populace as assessed using the Impact of Event Scale-Revised (IES-R) and Depression, Anxiety, and Stress Scale (DASS-21) [6]. Emerging adults are particularly at risk of mental health disorders as has been shown in prior studies done in 15 countries preceding the COVID-19 pandemic [7], and the risk is exacerbated during the pandemic due to the disruption of their day-to-day lives as reported in many studies [8,9]. Additionally, students have reported challenges with the shift from in-person classes to remote learning [10].…”
Section: Introductionmentioning
confidence: 67%
“…Based on a meta-analysis from studies conducted in 2020 and 2021, 34% of patients with COVID-19 experienced sleep disorders of varying severity [8]. A similar study of 582 students in Saudi Arabia found that 22% of them had problems falling asleep, 17.9% woke up in the night, 8.8% woke up early in the morning, 25.9% had poor sleep quality, 22.7% felt tired during the day, and about 10% had nightmares [9]. The results of multicenter studies demonstrated that insomnia was found in 36.7% of the subjects, and these ndings were about twice as high during the rst wave of the pandemic as the prevalence rates typically reported in nonpandemic times [10].…”
Section: Introductionmentioning
confidence: 99%